Ecosystem changes in deep Eastern Mediterranean: a comparison between 1989 and 2023 - Kostantchouk, Alessandra; Gambi, Cristina; Lo Martire, Marco; Corinaldesi, Cinzia; Dell’Anno, Antonio; Tangherlini, Michael; Danovaro, Roberto (Frontiers in Marine Science, 2025)
Major ecosystem changes have been observed in different oceanic regions and have also been reported in the deep sea as a result of complex physical and biological interactions. Here we investigated changes that have occurred in one of the world’s most oligotrophic regions: the deep Eastern Mediterranean Sea. Across a wide area of the Ionian and Aegean Sea, at depths ranging from 500 to 2500 m, we compared historical data dated back to 1989 with new data collected in 2023 exactly at the same sites. Changes in environmental variables (including surface water processes), and sediment organic matter content were related to the benthic response in terms of prokaryotic abundance, and the meiofaunal abundance and composition. We report here that, over this time frame of ca 30 years, this region experienced a progressive increase in bottom water temperatures and of the primary production in the photic zone, which may have determined the accumulation of protein and carbohydrate concentrations in surface sediments. Such changes resulted in an increase of prokaryotic abundance, but contrary to our expectation, were associated with a shift in the meiofaunal community structure and a decrease in the number of higher taxa. This included a reduction in evenness and a major decrease in meiofaunal biomass linked to the major decline of juvenile polychaetes. These results may indicate the altered functioning of the deep-sea ecosystems, with a potential loss of ecosystem services and a simplification of the benthic food webs.